BRICS Alliance: A SWOT Analysis and the Potential Implications for Ending the Dominance of the USD - A. Alrefai (BRICS Law Journal, 2024)
The group known as BRICS, comprising Brazil, Russia, India, China, and South Africa, came into being when its members decided to join hands to challenge the economic and political power of the wealthier nations of North America and Western Europe and expanded as BRICS+ when Egypt, Ethiopia, Iran, Saudi Arabia, and the United Arab Emirates entered the alliance with the same goals. Among the main reasons that led to the formation of the bloc was to put an end to the global dominance of the United States dollar (USD). Today, the BRICS+ bloc is motivated more than ever to find a solution to the ever-growing sanctions imposed by the United States (U.S.) on its member states as well as to cope with the fluctuating market situations that are merely based on the USD. The effectiveness of the newly expanded bloc’s alliance is the need of the hour, and for this purpose, the current study conducted a SWOT analysis to evaluate the bloc’s strengths, weaknesses, opportunities, and threats. The study took the facts and figures associated with the BRICS member states and their dealings with the U.S. and tried to analyze the effectiveness of this bloc should its members decide to conduct business with each other in a common currency. Furthermore, the study also evaluated the reasons behind the concept of de-dollarization and the benefits it offers the member states of the BRICS bloc. Additionally, the study proposes essential recommendations, such as the formulation of necessary measures to deal with potential disagreements that may arise regarding the choice of a common currency that should be used for trade among the member countries. Such an application of the study is an entirely novel application in the current area of research with the potential to open new horizons for future research considering the new targets of the BRICS+ group.